Relação entre eixos estruturantes da constituição psíquica e sustentação/ocupação de lugar de enunciação no processo de aquisição da linguagem - Bolzan, Renata Souto (2021)
This dissertation aimed to analyze the relationship between the axes of constitution of the psyche and the linguistic constitution of babies aged 3 to 24 months. For this, two studies were prepared, one with a quantitative nature and the other with qualitative case analysis. The first study sought to analyze the correlation between the structural axes of the psyche of the Risk Indicators/Reference to Child Development (IRDI) and language acquisition through the Enunciative Signals of Language Acquisition (SEAL) in data from 77 babies. The results obtained from the application of these two instruments were statistically analyzed using the Spearman coefficient and the Mann-Whitney U test, considering a p-value <= 0.05, in the comparison between the presence of enunciative signs and clinical indicators of the script IRDI There was statistical significance between changes in indicators related to maternal function (subject assumption, establishment of demand and alternation of presence/absence) and changes in the enunciative signs of babies and mothers. The second study aimed to investigate how the results obtained in the IRDI script (Clinical Reference Indicators/Risk to Child Development), in the SEAL (Enunciative Signs of Language Acquisition) and in the initial protoconversations in two babies with a history were uniquely related. of psychological distress in the first 18 months of life and different outcomes in language acquisition at two years of age. For analysis, the initial and continued interviews, the IRDI, the SEAL were used, as well as footage of the interaction between mother and baby. The results indicated that in the first case there was the existence of a separate subject assumption for operating the paternal function, with a progressive adjustment of synchrony in the mother-child dialogue, which allowed the overcoming of both psychological distress and the risk of language acquisition in the assessment of the second year of life. In the second case, however, there was a maternal abandonment of investment in dialogue, accompanied by the difficulty in operating the paternal function, that is, assuming a separate baby. In this case, there was no reversal of psychological distress and the baby presented a significant delay in language acquisition in the second year of life. Both the exercise of parental functions and the conditions of babies are important factors in their psychic and linguistic constitution, which brings important interdisciplinary reflections on the uniqueness in the relationship between these two aspects of child development.